New burnable absorber for long-cycle low boron operation of PWRs. (February 2016) - Choe, Jiwon; Shin, Ho Cheol; Lee, Deokjung
Highlights: A burnable absorber design for advanced PWRs with a low soluble boron concentration. The burnable absorber consists of a UO2 – 157 Gd2 O3 rod with a thin layer of Zr 167 Er2 . Three verification cases: two kinds of fuel assemblies and an OPR-1000 core. Abstract: This paper presents a new high performance burnable absorber (BA) design for advanced Pressurized Water Reactors (PWRs) aiming for a long-cycle operation with a low soluble boron concentration. The new BA consists of a UO2 – 157 Gd2 O3 rod covered with a thin layer of Zr 167 Er2 . A key feature of this new BA is that enriched isotopes, 157 Gd and 167 Er, are used as absorber materials. Since the high absorption cross section of 157 Gd can reduce the mass fraction of Gd2 O3 in UO2 –Gd2 O3, the thermal margin of fuel rods will increase with higher heat conductivity. Also, the 157 Gd transmutes into 158 Gd by neutron absorption and therefore the residual penalty at the end of cycle (EOC) will decrease. Since 167 Er has a resonance near the thermal neutron energy region, the moderator temperature coefficient (MTC) will become more negative and the control rod worth will increase. These advantages of the new BA are demonstrated with three verification cases: a 17 × 17 Westinghouse (WH) type fuel assembly, a 16 × 16 Combustion Engineering (CE) type fuel assembly, and an OPR-1000 equilibrium core.